EFEKTIFITAS INTERNATIONAL WHALING COMMISSION (IWC) DALAM PERBURUAN LUMBA-LUMBA ‘TAIJI DRIVE HUNT’ DI TAIJI JEPANG 2013 – 2017 - Addien Mirza Pratama; Marten Hanura (Journal of International Relations Diponegoro, 2019)
Dolphin hunting, or commonly called 'Taiji Drive Hunt' which is done massively in Taiji Region, Wakayama Prefecture, Japan occurred every year. Present the role of the IWC as an International Organization that can regulate the hunting of dolphins belonging to the cetacean’s category. Based on this background, the formulation of the problem that arises is "how effective is the organization of the International Whaling Commission (IWC) in the case of dolphin hunting in Taiji Japan?". This research aims to examine the effectiveness of the IWC which can also be said as an international regime that focuses on hunting cetaceans especially dolphins in 2013 to 2017. The results of this research are that state behavior is very crucial and culminates in the level of compliance within IWC organization, as well as the ambiguity in the International Convention for the Regulation of Whaling (ICRW) which causes misinterpretation among IWC members. In dealing the challenges of the effectiveness of IWC in the future, the author has several suggestions regarding cetaceans hunting, so that IWC further enforce the rules which have been previously agreed, so this organization can become better in carrying out their duties and functions. As for suggestions for the Japanese Government, it is expected to use a humane hunting method by not using dangerous tools in carrying out hunting practices for cetaceans, chiefly dolphins.